A Study of Linguistic Features of Proverbs Containing Weather Terms in English Versus Vietnamese - Nguyễn Thị Lựu (2012)
This thesis is conducted to investigate the semantic and syntactic features of proverbs containing weather terms in English versus Vietnamese. The object under investigation is proverbs containing weather terms ….